The Influence Of Employee Empowerment, Soft Skills And Hard Skills Towards Employee Performance In Hotel/ Hospitality Industry - Anthonius, Anthonius (Universitas Muhammadiyah Tangerang, 2021)
The growth and competition of Indonesia’s hotel industry, especially during the Covid-19 pandemic, has hardly pushed them to maintain their corporate and employee performance. The factors related to human resource and hospitality industry, which cloud significantly affects the employee’s performance are employee empowerment, soft skill and hard skill. This research is a quantitative research with hypothesis test. The samples used are 100 active employees of 4 stared rated hotels. This research uses questionnaire as the research instrument and the data analysis conducted by applying Structural Equation Modeling (covariances based SEM). This research contributes to Indonesia’s hotel industry by stating that while the employee empowerment factor has no impact toward the employee performance, both the hard and soft skill factors are positively impacting the employee’s performance in Indonesia’ hotel industry.